Bridged tolanes: a twisted tale - Menning, Sebastian; Krämer, Maximilian; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (The journal of organic chemistry, 2014)
The rotational motion of tolanes along their acetylene axis is not fully understood. What happens to the optical and electronic properties if the tolane backbone is forced into a twisted conformation? Several tethers were investigated to obtain tolanophanes, fixing the torsion angle of the two phenyl rings. X-ray crystal structures revealed tether-specific torsion angles in the solid state. The absorption, emission, and excitation spectra were recorded. Twisted tethered tolane conformers showed blue-shifted absorption; emission spectra were all torsionally independent and identical. The tethered tolanes were embedded in a rigid matrix by freezing to 77 K; well-resolved emission spectra were recorded for planar tolanes, but for twisted systems unexpectedly long-lived phosphorescence was observed. How is this triplet emission explained? Quantum chemical calculations (TDDFT/cam-B3LYP/6-31G*) of the unsubstituted tolane showed that intersystem crossing (ISC) is favored with large spin-orbit coupling, which occurs when the molecular orbitals are orthogonal to each other; this is the case at the crossing of S1/T7. Also, a small energy difference between singlet and triplet states is required; we found that ISC can favorably take place at four crossings: S1/T6, S1/T7, S1/T8,9, S1/T10.